Fish Oil Supplementation in Pregnancy Increases Gestational Age, Size for Gestational Age, and Birth Weight in Infants: A Randomized Controlled Trial. Issue 4 (9th November 2018) - Vinding, Rebecca Kofod; Stokholm, Jakob; Sevelsted, Astrid; Chawes, Bo L; Bønnelykke, Klaus; Barman, Malin; Jacobsson, Bo; Bisgaard, Hans
ABSTRACT: Background: Randomized trials have reported that supplementation with n–3 long-chain polyunsaturated fatty acids (LCPUFAs) in pregnancy can prolong pregnancy and thereby increase birth weight. Objective: We aimed to examine the relations of n–3 LCPUFA supplementation in pregnancy with duration of pregnancy, birth weight, and size for gestational age (GA). Methods: This was a double-blind randomized controlled trial conducted in 736 pregnant women and their offspring, from the Copenhagen Prospective Studies on Asthma in Childhood2010 cohort. They were recruited between weeks 22 and 26 in pregnancy and randomly assigned to either of 2.4 g n–3 LCPUFA or control (olive oil) daily until 1 wk after birth. Exclusion criteria were endocrine, cardiovascular, or nephrologic disorders and vitamin D supplementation intake >600 IU/d. In this study we analyzed secondary outcomes, and further excluded twin pregnancies and extrauterine death. The primary outcome for the trial was persistent wheeze or asthma. Results: The random assignment ran between 2008 and 2010. Six hundred and ninety-nine mother-infant pairs were included in the analysis. n–3 LCPUFA compared with control was associated with a 2-d prolongation of pregnancy [median (IQR): 282 (275–288) d compared with 280 (273–286) d, P  = 0.02], a 97-g higher birth weight (mean ± SD: 3601 ± 534 g compared with 3504 ± 528 g, P  = 0.02), and an increased size for GA according to the Norwegian population-based growth curves-Skjærven (mean ± SD: 49.9 ± 28.3 percentiles compared with 44.5 ± 27.6 percentiles, P  = 0.01). Conclusion: Supplementing pregnant women with n–3 LCPUFAs during the third trimester is associated with prolonged gestation and increased size for GA, leading to a higher birth weight in this randomized controlled trial. This trial was registered at clinicaltrials.gov as NCT00798226.